Theoretically Predicted and Experimentally Observed Relaxation Pathways of two Heterodinuclear 3d‐4f Complexes12. Issue 12 (21st September 2015) - Bender, Markus; Comba, Peter; Demeshko, Serhiy; Großhauser, Michael; Müller, Dennis; Wadepohl, Hubert
Abstract: The dinucleating ligand (1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetrayl)‐tetrakis‐(methylene)‐tetrakis(2‐methoxy‐4‐methylphenol), H4 L, is well preorganized with an N4 O2 octahedral site for a divalent transition metal ion and an O4 site (phenolates and methoxo donors, completed by added pivalates and solvent molecules) for lanthanide ions. Two 3d‐4f complexes ([Dy III {Ni II (μ‐H2 L)}piv2 (OH2 )]ClO4 and [Dy III {Co II (μ‐H2 L)}piv2 (OH2 )]ClO4 ) were prepared and fully characterized by X‐ray molecular structures and electronic properties determined by ac and dc SQUID magnetometry. While the Ni II based complex shows single‐molecule magnetism (SMM), the Co II complex does not. With an extensive quantum‐chemical analysis, this is shown to be due to a misalignment of the single ion anisotropies in the latter complex, and reasons for this are discussed. Abstract :